Pengaruh Pelatihan Kerja dan Motivasi Kerja terhadap Kinerja Therapist pada PT XYZ : The Effect of Job Training and Work Motivation on Therapist Performance at PT XYZ - Fariza Ananta; Lela Elvira; Maria Lapriska Dian Ela Revita (PT Cakrawarti Empat Proksi, 2026)
This study aims to analyze the influence of job training and work motivation on therapist performance at PT. XYZ. The main problem in this study focuses on how employee technical competence and psychological motivation contribute to the company's service quality. The research method used was a quantitative approach. Data were collected from 69 respondents who were therapists at PT. XYZ. Data analysis was performed using the t-test for partial testing and the f-test for simultaneous testing, as well as coefficient of determination analysis. The results showed that partially, job training had a positive and significant effect on therapist performance (t-test 4.165 > t-table 1.997; p < 0.05). Similarly, work motivation had a positive and significant effect on performance (t-test 2.879 > t-table 1.997; p < 0.05). Simultaneously, these two variables significantly influenced therapist performance, with a calculated f-value of 21.328 (calculated f>ftable 3.14) and a significance level of 0.000. The coefficient of determination (R2) value was 0.393, indicating that job training and work motivation explained 39.3% of the variance in performance, while the remaining 60.7% was influenced by factors outside the scope of this study. In conclusion, improving the quality of training programs and strengthening work motivation will effectively drive therapist performance at PT. XYZ.